Influence of preoperative femoral orientation on radiographic measures of femoral head height in total hip replacement. (January 2021) - O'Connor, John D.; Hill, Janet C.; Beverland, David E.; Dunne, Nicholas J.; Lennon, Alex B.
Abstract: Background: In total hip arthroplasty the surgeon aims to restore the biomechanics of the joint. Femoral height has the greatest influence on restoring limb length and contributes equally to the restoration of femoral head centre. On X-ray, the level of femoral neck resection is most often referenced off the upper border of lesser trochanter. Less frequently, femoral head centre is referenced from the tip of the greater trochanter. The error in measurement of femoral height resulting from unknown femoral rotation is crucially important and can result in inappropriate surgical planning for implant selection and placement. It is unknown which reference produces lower error. Methods: A sample of femoral shapes was generated using a femoral statistical shape model. These were placed in a range of orientations in terms of external rotation and flexion, at intervals of 10°. Simulated X-rays were then produced and the distances from the tip of either greater or lesser trochanter to femoral head centre were measured. Findings: Although using greater trochanter as a reference demonstrated greater errors at the extremes, both techniques resulted in errors of 7–8 mm with 20° of both femoral external rotation and flexion. Interpretation: Moderate degrees of femoral external rotation combined with flexion can result in unsatisfactory errors when templating limb length. There should be greater focus and an agreed definition for femoral height. There is a clinical need for a method with a lower error in determining true femoral height and the level of neck resection. Highlights: Little focus on femoral head height in total hip arthroplasty. Relative reliability of radiographic landmark references unknown. This simulation study modelled different femoral orientations. Error shown to be common and greater trochanter more sensitive to rotation.